The use of website for teaching and learning English in industrial practice students of vocational high school - Parto Sasmito; Imam Ghozali (Universitas Sarjanawiyata Tamansiswa, 2021)
Abstract: This study aims to describe the use of website for teaching and learning English and to reveal the efficacy of using website media in learning English in class XI students of State Vocational School of 5 Bojonegoro, competency of agricultural product processing agribusiness skills. The method used in this research is a descriptive qualitative case study, with data obtained from interview recordings of informants consisting of the principal, English teacher, and eleventh-graders, and documentation. The findings show that the use of the website in agribusiness agricultural product processing class in teaching and English were effective because they carried out industrial work practices they could still attend lessons anywhere and anytime during breaks or at home. The obstacle faced is the problem of poor internet network when accessing the website. The same thing for teachers, can provide teaching materials and conduct evaluations anytime anywhere with the website. Obstacles encountered by teachers when students do not open the website, the teacher must find out the reasons students do not follow the learning process through the website. When students are carrying out industrial work practices, students' concentration is indeed focused on these activities. Keywords: information and communication technology, teaching English, website.